Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_81_90
|View full text |Cite
|
Sign up to set email alerts
|

Linking the Properties, Processing and Chemistry of Advanced Single Crystal Ni-Base Superalloys

Abstract: As nickel-base single crystals are being implemented in gas turbine engines operating at temperatures in excess of 1600K, maintaining structural properties at these elevated temperatures has become an increasingly important problem. Typically, elevated levels refractory alloying elements are added to these single crystal alloys to enhance the degree of solid solution strengthening within the microstructure. The presence of Re, W, Mo, Ta in Ni-base superalloys strongly influences parameters, such as the stackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…It should be noted that the superalloy composition is close to that of some single-crystal superalloys and casting superalloys [1,48]. The present work demonstrated that heavy alloying of nickel-base superalloys with refractory elements including rhenium is not contraindicative for wrought processing.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…It should be noted that the superalloy composition is close to that of some single-crystal superalloys and casting superalloys [1,48]. The present work demonstrated that heavy alloying of nickel-base superalloys with refractory elements including rhenium is not contraindicative for wrought processing.…”
Section: Resultssupporting
confidence: 73%
“…To improve the fuel efficiency of GTE, it is of great importance to develop new Ni-based superalloys to withstand higher operating temperatures and loadings [13]. Regarding polycrystalline nickel-base superalloys, which are the most competitive from the viewpoint of the production cost, novel nickel-base superalloys are often designed towards heavier alloying [111]. Particularly, the alloy designing approaches include an increase in the volume fraction of the γ′ phase precipitates by increased concentrations of precipitate forming elements [1,2], heavy alloying with elements providing effective substitutional solid solution strengthening and a higher γ′ solvus temperature [1,46] etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also known that there is a strong correlation between the level of refractory alloying additions, such as Mo, Hf, Ta, W and Re in CMSX-10 in this study, and the occurrence of the freckle chains 44) . Therefore, solute segregation probably induces the buoyancy driven convective uid ow and result in the formation of freckle defects during dendritic solidi cation 44) . However, despite much research on the nature of freckle chains, there is little literature showing the boundary of freckle chains and matrix.…”
Section: Detection Of Re-rich Particles At Freckle Chainsmentioning
confidence: 98%
“…As already predicted by the calculations, the literature data supports that Nb and Mo additions to the alloy composition are expected to govern the formation of the TCP Laves phase 26 , 27 . Additionally, it is expected that Nb further increases the APB energy of the -phase 28 , 29 and Mo contributes to the solid solution strengthening (SSS) 17 , 30 of the multi-component matrix, further contributing to material strength at elevated temperatures. It is also reported that both elements increase the lattice parameter in the CCA’s matrix 31 , leading to a lower lattice misfit between the matrix and the -phase, as the latter commonly exhibits a larger lattice parameter in these types of alloys 3 , 32 .…”
Section: Resultsmentioning
confidence: 99%